The Citra perempuan ningrat dalam novel Panggil Aku Kartini Saja karya Pramoedya Ananta Toer: kajian simbolik Roland Barthes - Siti Bagja Muawanah; Siti Ansoriyah; Siti Gomo Attas (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
This research aims to understand the image of noble women contained in the novel “Panggil Aku Kartini Saja” by Pramoedya Ananta Toer using Roland Barthes' Symbolic study. This research uses a descriptive qualitative method. The data collection techniques used are description method and literature research. The data analysis technique used in this research is descriptive-analytic. The result of the research that has been carried out is that there are 60 lexia found in the novel “Panggil Aku Kartini Saja” by Pramoedya Ananta Noer, which are spread into three kinds of Roland Barthes symbolic studies in the form of 45 lexia antithetical, 12 lexia 'kemenduan', and 3 lexia opposition of two elements. The whole lexia illustrates that Kartini is a noblewoman who has an image: upholding the religion she adheres to, loving her father, and fighting for the interests of the people by writing and establishing special schools for women, a product of the shift in eastern and western culture, likes to read, and so on.